Nanomaterial safety in the workplace : pilot project for assessing the impact of the NIOSH Nanotechnology Research Center - Landree, Eric (Research report (Rand Corporation), 2015)
"In August 2014, the National Institute for Occupational Safety and Health (NIOSH) Nanotechnology Research Center (NTRC) asked the RAND Corporation to help develop and apply a method for assessing the center's contribution to improving the safety and health of workers who could be affected by the production, use, reuse, or disposal of the products of nanotechnology that are of greatest concern to workers, such as engineered nanomaterials. The purpose of the project was to develop a method that would help NTRC - and other NIOSH components - get beyond conventional bibliometric and patent analysis and closer to societal benefit or outcomes, in part by looking to the gray literature, professional events, and stakeholder outreach for supplemental evidence. Using a logic model, this report outlines a method for NTRC to collect, organize, and assess information related to its program efforts and how they are contributing to NIOSH's desired outcome of reducing injuries, illnesses, and fatalities associated with occupational exposure to engineered nanomaterials. Based on our pilot study, we identified several plausible paths by which intermediate customers may use NTRC outputs to contribute to NIOSH's mission, and we highlighted the role of NTRC field research teams in contributing to changes in workplace practices and procedures."--Back cover